CIPP Analysis of the Implementation of Project-Based Learning Assisted by Kahoot in Differentiated Classrooms - Suciati, Suciati; Sucipto, Sucipto; Tobing, Victor Maruli Tua L; Sulastri, Sulastri; Purnamasari, Hetty (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
The 21st century competencies identified by the Partnership for 21st Century Skills (P21) include communication, collaboration, critical thinking, and creativity. However, the achievement of these competencies is often hampered by the lack of student learning motivation. This study aims to evaluate the application of project-based learning (PjBL) assisted by Kahoot media in differentiated learning in class IX-H MTsN Bangkalan. The type of research used is descriptive qualitative with a CIPP (Context, Input, Process, Product) evaluation approach. The results showed that choosing the right learning media context can increase student motivation and creativity. Innovation in PjBL learning combined with differentiated learning is proven to increase active student involvement. The well-planned learning process reflects the success of classroom management by the researcher. In addition, the achievement of evaluation results shows that students feel more motivated and enthusiastic in participating in learning and show increased creativity in the assigned tasks. The fun assessment atmosphere also contributed to the positive learning experience. The implication of this study shows that the implementation of PjBL with Kahoot media can be an effective strategy to increase students' motivation and engagement in differentiated learning